Fish Swimming Behavior and Bypass Acceptance at Curved-Bar Rack Bypass Systems - Beck, Claudia; id_orcid:0 000-0001-9021-1378; Albayrak, Ismail; id_orcid:0 000-0002-4613-6726; Meister, Julian; id_orcid:0 000-0002-2715-6780; Peter, Armin; Selz, Oliver M.; Leuch, Claudia; id_orcid:0 000-0003-3293-1734; Vetsch, David F.; id_orcid:0 000-0003-3293-5831; et al. (International Association for Hydro-Environment Engineering and Research, 2022)
The present study deals with the hydraulic and fish-biological performance of an innovative curved-bar rack bypass system (CBR-BS). CBR is a mechanical behavioral fish guidance structure typically combined with a BS, that was developed at VAW of ETH Zurich for safe downstream fish passage at hydropower plants. A hydraulically optimized CBR with a full-depth BS was tested with six European fish species, namely, spirlin, nase, barbel, Atlantic salmon parr, brown trout and European eel in an ethohydraulic laboratory flume. The approach flow velocities were 0.50 and 0.70 m/s and the velocity ratios (VR) of mean bypass inlet velocity to mean approach flow velocity were 1.2 and 1.4 for each flow velocity, resulting in four different hydraulic conditions. The flow field around the CBR-BS was numerically simulated for each hydraulic condition with a CFD model. The simulation results show that the velocity gradients between the curved bars and up to ~40 mm upstream from the rack are high. The live-fish tests showed that such high velocity gradients triggered an avoidance reaction of spirlin, nase, barbel, salmon parr and partly brown trout, but not of eel. Fish guidance and protection efficiencies of the CBR-BS were higher than 75% for spirlin, barbel, nase and Atlantic salmon parr, whereas they were lower than 75% and 50% for brown trout and European eel, respectively. Increasing VR from 1.2 to 1.4 significantly decreased the number of bypass passages underlining the importance of bypass design. Recommendations for an optimized and economic CBR-BS design are given.